2004
DOI: 10.1158/1078-0432.ccr-04-0488
|View full text |Cite
|
Sign up to set email alerts
|

Using Protein Expressions to Predict Survival in Clear Cell Renal Carcinoma

Abstract: Purpose: An accurate system for predicting survival for patients with solid tumors will allow for better patient selection for both established and novel therapies. We propose a staging system for clear cell variants of renal cell carcinoma (RCC) that includes molecular predictors and standard clinical predictors such as tumor-node-metastasis (TNM) stage, histological grade, and performance status (PS).Experimental Design: A custom tissue array was constructed using clear cell RCC from 318 patients, representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(132 citation statements)
references
References 31 publications
5
124
1
2
Order By: Relevance
“…In breast and gall bladder cancer, patients with high Ep-CAMexpressing primary tumours indeed showed a decreased survival (Gastl et al, 2000;Spizzo et al, 2002;Spizzo et al, 2004;Varga et al, 2004). In clear cell renal cell carcinoma, Ep-CAM expression is infrequent, but patients with Ep-CAM overexpressing tumours show a trend to better survival (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005). A similar correlation was reported for gastric cancers (Songun et al, 2005).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…In breast and gall bladder cancer, patients with high Ep-CAMexpressing primary tumours indeed showed a decreased survival (Gastl et al, 2000;Spizzo et al, 2002;Spizzo et al, 2004;Varga et al, 2004). In clear cell renal cell carcinoma, Ep-CAM expression is infrequent, but patients with Ep-CAM overexpressing tumours show a trend to better survival (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005). A similar correlation was reported for gastric cancers (Songun et al, 2005).…”
supporting
confidence: 54%
“…Epithelial cell adhesion molecule upregulation was an independent marker for poor survival in lymph node positive breast cancers , and gall bladder cancers (Varga et al, 2004). In contrast, improved survival was found associated with Ep-CAM upregulation in clear cell renal cell carcinoma (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005), and gastric cancers (Songun et al, 2005). Here, we observed that survival of patients in the subgroup of moderately differentiated colon cancers also showed a significant positive correlation with Ep-CAM expression.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…5,6 Another TMA study on clear cell RCC from 318 patients suggested, upon a multivariate analysis, that only metastatic status (M=1, or n>0), gelsolin, p53 and metastatic status/CAIX remained significant predictors of survival. 19 In a similar analysis CAIX, vimentin and p53 were statistically significant predictors of survival independent of the clinical variables. 22 A model using comparative genomic hybridization (CGH), a molecular screening method permitting the detection of all DNA losses and gains in a tumor, suggested that there may be at least two subclasses of clear cell RCC: one marked by the events -6q, +17q, +17p, and the other by -9p, -13q, -18q.…”
Section: Genetic Changes During Tumor Growth and Progressionmentioning
confidence: 79%
“…Although the administration of IL-2 offers the possibility of durable CRs, it is associated with considerable toxicity, while only a small subset of patients respond to therapy 3 . Possible biomarkers for RCC such as carbonic anhydrase-IX (CA IX), Ki67 or PTEN have been published 6,7 . However, there is no reliable single marker available to identify those patients that are more likely to respond to IL-2 therapy, although factors such as regional lymphadenopathy, expression of CA-IX 8,9 , and selective pathologic subtypes have been proposed 10 .…”
Section: Purposementioning
confidence: 99%